Estrategias para optimizar la aplicación de los recursos didácticos en la asignatura de Cultura Física en el centro educativo particular mixto Hispanoamericano del cantón Santa Rosa, provincia de El Oro, periodo lectivo 2011 - 2012. - Mora Álvarez, Milena Lesseth (2015)
This thesis entitled Strategies for optimizing APPLICATION OF TEACHING RESOURCES IN THE COURSE OF PHYSICAL CULTURE IN Coeducational Private School HISPANOAMERICANO CANTON SANTA ROSA, El Oro province, school period 2011 - 2012 that highlights the same importance of the application of teaching resources when teaching the physical education classes, optimizing strategies for the development of the activities planned by the teacher.